МОДЕЛЮВАННЯ ЕЛЕКТРОМАГНІТНИХ ПРОЦЕСІВ В СЕКЦІЙНОМУ КРИСТАЛІЗАТОРІ ДЛЯ ЕЛЕКТРОШЛАКОВОГО НАПЛАВЛЕННЯ МЕТАЛУ - Гориславець, Ю.М.; Бондар, О.І.; Проскудін, В.М.; Кусков, Ю.М.; Римар, С.В.; Нетяга, А.В. (Інститут електродинаміки НАН України, Київ, 2022)
A three-dimensional mathematical model for the study of electromagnetic processes occurring in a sectional current-supply crystallizer during electroslag surfacing of metal is presented. Numerical simulations of the electromagnetic field in such system were performed, the distributions of electric current density, volumetric heat emissions in the system elements, as well as the distribution of electromagnetic forces in liquid slag were obtained. The comparison of calculated and experimental values of the integral parameters of the specified system is carried out. References 8, figures 5, tables 2.